LGG-35. Dyslipidemia in children treated with BRAF inhibitors for brain tumor, a new side effect? A single center retrospective study. (3rd June 2022) - Crocco, Marco; Verrico, Antonio; Milanaccio, Claudia; Piccolo, Gianluca; Gaggero, Gabriele; De Marco, Patrizia; Iurilli, Valentina; Profio, Sonia Di; Calevo, Maria Grazia; Casalini, Emilio; Iorgi, Natascia Di
Abstract: The targeted therapies for brain tumors are innovative and promising oncological treatments and as a result their use has expanded widely. BRAF inhibitors (BRAFi) in recent years have played a central role in disease control of unresectable BRAF-mutated pediatric low-grade gliomas (LGG). Understanding the side effects of these drugs is crucial for clinical practice. The aim of the study was to investigate retrospectively the acute and long-term effects of vemurafenib on lipid metabolism in children treated for an LGG. Children (n=6) treated with vemurafenib at the mean age of 8.41±6.1 exhibited early alterations in plasma lipid profile as demonstrated after 1 month (n=4) by high plasma levels of Low-Density Lipoprotein (LDL 139.5±51.5, mg/dL), Total Cholesterol (TC 221.5±42.1, mg/dL) and Triglycerides (TG 107.8±44.4, mg/dL). Despite dietary recommendations, dyslipidemia persisted 3 months later (LDL 148.8±40.2, mg/dL; TC 238±36.5, mg/dL; TG 115±45.6, mg/dL; n=4) and at long distance follow-up (38±23, months) after treatment with vemurafenib: LDL 139.2±49.1, mg/dL; TC 216.5±38.4, mg/dL; TG 129.7±83.4 mg/dL. This potential side effect suddenly resolved itself in the only patient in which a change of therapy was made (to the combination of dabrafenib and trametinib). BMI was compatible with overweight/obesity at baseline (mean BMI-SDS 0.9±1.8) in 2 patient and normal in 4 patients: during follow-up BMI remained stable in 5 patients and increased in 1 patient. Our findings highlight that Vemurafenib could be associated with an increased risk of dyslipidemia independently of weight. This risk should be anticipated by the identification of high-risk patients and managed by close monitoring of metabolic parameters during routinely follow-up. The association of dabrafenib with trametinib seem not be associated to dyslipidemia, yet more data are needed to explore the hypothesis about the possible role to reduce the risk of dyslipidemia.